INCIDENCE OF URINARY TRACT INFECTION DURING PREGNANCY - Khaliq, M.A.; Pervez, Shaheen; Begum, Nazakat; Bano, Aniqa (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: Incidence of Urinary tract infection was determined in 164 pregnant women presented at DHQ Teaching Hospital, Abbottabad. The cases with significant bacteriuria (> 10 5 organisms/ml of Urine) were 9.7% of total. 76% of the patients were less than 30 years of age with mean of 28 years. In the symptomatic group the frequency of UTI was 12.5% while in the asymptomatic group it was about 4.0%. Pyuria was found in 13.4% of the total cases. Albumin and Glucose in Urine were found to be 6% and 3% respectively. The organisms isolated were E. Coli (56.3%) Staphylococcus (25.0%) Klebsiella Spp (12.5%) and proteus Spp (6.2%). Most of them were sensitive to Minocin, Gentamycin, Claforan, whereas the sensitivity to Amoxil, Dalacin, Fosfomycin and Doxycyclin was variable.